Thermo-economic feasibility study to utilize ORC technology for waste heat recovery from Indian nuclear power plants - Srivastava M.; Sarkar J.; Sarkar A.; Maheshwari N.K.; Antony A. (My University, 2025)
A feasibility study is essential before installing a power generation system to recover waste heat from nuclear power plants, but not yet been done. Hence, nine possible waste heat locations of Indian nuclear power plants are identified and two feasible cases (case-1 and case-2) are deduced to use the organic Rankine cycle (ORC) as a bottoming cycle. Energy, exergy, economic and environmental performances are evaluated for feasible cases with three working fluids. Capital investment in alternator has been correlated based on market data and applied in economic analysis. The economic study is based on Net present value, Discounted payback period, Levelized cost of energy, Internal rate of return, Profit and per unit build-up cost of ORC to suggest whether the installation is worth to venture or not. The result shows that below 41 °C condenser temperature, case-2 based bottoming ORC should be the priority to install and at the availability of sufficient funds, both cases can be installed, which will cumulatively produce 486.2 kW of electricity from waste energy with a total of 201.14 thousand USD annual profit from the total capital investment of 723.74 thousand USD. In 40 years of the project's lifetime, a total of 1.317 million USD will be used if both cases are employed and the invested cost will be returned in 8.3 years. © 2024 Elsevier Ltd